A robust fault-tolerant and scalable cluster-wide deduplication for shared-nothing storage systems - Khan, Awais; Lee, Chang Gyu; Hamandawana, Prince; Park, Sungyong; Kim, Youngjae (Proceedings - 26th IEEE International Symposium on Modeling, Analysis and Simulation of Computer and Telecommunication Systems, MASCOTS 2018, 2018)
Deduplication has been largely employed in distributed storage systems to improve space efficiency. Traditional deduplication research ignores the design specifications of shared-nothing distributed storage systems such as no central metadata bottleneck, scalability, and storage rebalancing. Further, deduplication introduces transactional changes, which are prone to errors in the event of a system failure, resulting in inconsistencies in data and deduplication metadata. In this paper, we propose a robust, fault-Tolerant and scalable cluster-wide deduplication that can eliminate duplicate copies across the cluster. We design a distributed deduplication metadata shard which guarantees performance scalability while preserving the design constraints of shared-nothing storage systems. The placement of chunks and deduplication metadata is made cluster-wide based on the content fingerprint of chunks. To ensure transactional consistency and garbage identification, we employ a flag-based asynchronous consistency mechanism. We implement the proposed deduplication on Ceph. The evaluation shows high disk-space savings with minimal performance degradation as well as high robustness in the event of sudden server failure.
Keywords: Data de duplications; Design constraints; Design specification; Distributed and cloud computing; Distributed storage system; File systems; Performance degradation; Performance scalability; Data Deduplication; Distributed and cloud computing; Distributed Storage Systems; Storage and file systems